2006
DOI: 10.1242/jcs.02858
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell motility is triggered by activation of the EGF receptor through phosphatidic acid signaling

Abstract: Phospholipase D catalyzes the hydrolysis of phosphatidylcholine to generate phosphatidic acid, and there is currently much interest in elucidating messenger functions for this molecule. We report here that wounding sheets of corneal epithelial and Madin Darby canine kidney cells induces strong activation of phospholipase D, and we provide evidence that activation is amplified through a positive feed-back loop. Short-chain analogues of phosphatidic acid induce motility robustly in corneal and other epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 66 publications
2
34
1
Order By: Relevance
“…We have studied the mechanism of PLD-induced chemotaxis and found that the enzymatic activity of the lipase needs to be intact. This is in agreement with the findings of Mazie et al (43), who demonstrated that EGF triggers the activation of PLD in MDCK cells. PA, the product of PLD activation, is a critical mediator of EGF-dependent cell motility.…”
Section: Discussionsupporting
confidence: 94%
“…We have studied the mechanism of PLD-induced chemotaxis and found that the enzymatic activity of the lipase needs to be intact. This is in agreement with the findings of Mazie et al (43), who demonstrated that EGF triggers the activation of PLD in MDCK cells. PA, the product of PLD activation, is a critical mediator of EGF-dependent cell motility.…”
Section: Discussionsupporting
confidence: 94%
“…Wounded corneal epithelial cells undergo an EMT as cells migrate at the leading edges of the wound. Treatment with exogenous PtdOH or overexpression of PLD2 caused a dramatic reduction of cell surface E-cadherin in these cells (Mazie et al, 2006). However, butanol did not decrease EGF stimulation of ERK in this system, suggesting that PLD may regulate E-cadherin through different means.…”
Section: F Activating Invasion and Metastasismentioning
confidence: 75%
“…As such, butanol treatment or knockdown of PLD is associated with defects in the ability to form adhesions (Aguirre Ghiso et al, 1997;Iyer et al, 2006). The speed of migration is largely controlled by the speed at which cells form and detach from these adhesions (Lauffenburger and Horwitz, 1996) and PLD regulates migration speed in wound-healing assays (Mazie et al, 2006). PLD activity is associated with an increase in vinculin levels (Mazie et al, 2006) as well as activation of focal adhesion kinase, a key regulator of focal adhesion turnover (Lli c et al, 1995;Knoepp et al, 2008).…”
Section: F Activating Invasion and Metastasismentioning
confidence: 99%
“…1,2-Dioctanolyl-glycero-3-phosphate (C 8 -PA) is a water-soluble synthetic phosphatidic acid that traverses the plasma membrane and mimics the effects of phospholipase D expression (Mazie et al, 2006). We added C 8 -PA to the media of HeLa cells at 24 h after HeLa cells were either untreated (Cells), exposed to Lipofectamine RNAiMAX alone (Lipo) or transfected with scrambled control (Ctrl siRNA) or choline kinase-a-specific siRNA (CK siRNA) for 48 h. The cells were then examined for (a) choline kinase-a and choline kinase-b mRNA expression using real-time reverse transcriptase (RT)-PCR (normalized to b-actin), (b) choline kinase protein expression using western blot and (c) phosphocholine (PCh) using nuclear magnetic resonance (NMR).…”
Section: Inhibition Of Choline Kinase Expression Disrupts Signaling Pmentioning
confidence: 99%